The Impact of Corporate Monopolies on Market Competition and Economic Health - Nimatullayev, Khondamir; Avazov, Ilkhom (GREEN ECONOMY AND DEVELOPMENT, 2023)
This article critically examines the implications of corporate monopolies on market competition and economic health. It explores the multifaceted problems arising from the dominance of a few corporations in various sectors, emphasizing the consequences for consumer choice, pricing, innovation, and political influence. The article also provides a forward-looking perspective, proposing potential solutions to mitigate the adverse effects of monopolistic practices.